2018
DOI: 10.1016/j.ijsu.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Perforated diverticulitis: To anastomose or not to anastomose? A systematic review and meta-analysis

Abstract: Resection and primary anastomosis should be considered as a feasible and safe operative strategy in selected patients with perforated diverticulitis. There is however a paucity of high level evidence and further research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
3
10
0
3
Order By: Relevance
“…In our series, both rectal stump leakages developed in elderly and frail patients after HP for Hinchey IV diverticulitis. The incidence of anastomotic leak in our study was 4.6% and was similar to that found in the literature [32]. In all these cases, the patients were not immunosuppressed and no intraoperative complications were documented.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our series, both rectal stump leakages developed in elderly and frail patients after HP for Hinchey IV diverticulitis. The incidence of anastomotic leak in our study was 4.6% and was similar to that found in the literature [32]. In all these cases, the patients were not immunosuppressed and no intraoperative complications were documented.…”
Section: Discussionsupporting
confidence: 91%
“…In the analysis of his multicenter study, the author complained about the refusal of some surgeons to randomize ill patients, as a result of their skepticism in the applicability of PA in patients with generalized peritonitis [38]. This resulted in poor recruitment and premature termination of the trial, before achieving the planned sample size as highlighted in a meta-analysis by Shaban et al, who stated that the included RCTs were underpowered [32].…”
Section: Discussionmentioning
confidence: 99%
“…The present results are generally in line with those from previous meta-analyses. With regard to overall mortality from randomized and observational studies, Gachabayov et al [34] and Shaban et al [35] found PA to be favorable over HP, which was also the case in the present quantitative analysis of mortality within the included observational studies. However, in the subgroup analysis of randomized studies in a b c Fig.…”
Section: Discussionsupporting
confidence: 81%
“…In perforated diverticulitis, for example, there has been no consensus in the management, which is why the Shaban and coauthors [19] felt compelled to perform a systematic review and meta-analysis, particularly because many surgeons choose the Hartmann's procedure to avoid the risk of an anastomotic leak.…”
Section: The Anastomosis In An "Emergency" Setting Scared Of a (Potential)mentioning
confidence: 99%